Turkey: Change from an emigration to an immigration and now to a transit migration country - Secil Pacaci Elitok; Thomas Straubhaar (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2010)
In the post Second World War period Turkey was an emigration country for a long time. But things have changed since. After the end of the Cold War and the breakup of the Soviet Union, immigration from the neighborhood to Turkey increased substantially. A lively cross-border movement with the countries of the former Soviet Union, but also with the Middle East countries (i.e. especially Iran), has occurred. On the other hand, Western European countries have become extremely reluctant to open up their borders to Turkish migrants. As a consequence, Turkey is a country of emigration, immigration and transit, nowadays. In this paper, we concentrate on immigration and transit migration.
Keywords: 330